2006
DOI: 10.1159/000090835
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mouse conceptuses with uniparental duplication/deficiency for distal chromosome 12: comparison with chromosome 12 uniparental disomy and implications for genomic imprinting

Abstract: Distal mouse chromosome 12 is imprinted. Phenotypic analysis of mouse embryos with maternal or paternal uniparental disomy for the whole of chromosome 12 has characterized the developmental defects associated with the altered dosage of imprinted genes on this chromosome. Here we conduct a characterization of maternal and paternal Dp(dist12) mice using the reciprocal translocation T(4;12)47H. This limits the region analysed to the chromosomal domain distal to the T47H breakpoint in B3 on mouse chromosome 12. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Lack of methylation anomalies at the imprinting control region (IG DMR) of the chromosome 12 imprinted cluster suggests that either another DMR from the same domain or another imprinted domain is involved. The latter possibility is not an unlikely one because the distal part of chromosome12 harbors several imprinted regions, only one of which has been characterized in detail (Tevendale et al 2006). Moreover, we cannot rule out the possibility that an epigenetic mechanism distinct from genomic imprinting is responsible for the grandparental origin effects on allelic transmission in the distal region of chromosome 12.…”
Section: Discussionmentioning
confidence: 91%
“…Lack of methylation anomalies at the imprinting control region (IG DMR) of the chromosome 12 imprinted cluster suggests that either another DMR from the same domain or another imprinted domain is involved. The latter possibility is not an unlikely one because the distal part of chromosome12 harbors several imprinted regions, only one of which has been characterized in detail (Tevendale et al 2006). Moreover, we cannot rule out the possibility that an epigenetic mechanism distinct from genomic imprinting is responsible for the grandparental origin effects on allelic transmission in the distal region of chromosome 12.…”
Section: Discussionmentioning
confidence: 91%
“…Defective vascularisation of the paternal UPD labyrinth occurs by E15.5, with an increased abundance of glycogen cells at E13.5 that fail to appropriately invade the decidua and do not decline in number towards term as normal (Georgiades et al 2001). The placental defects can be traced to the most distal region of chromosome 12, with paternal UPD of this region associated with placentomegaly and maternal UPD associated with a placental weight deficit similar to those observed for UPD of the entire chromosome (Tevendale et al 2006).…”
Section: Distal Chromosome 12mentioning
confidence: 81%
“…Such studies suggested the presence of imprinted genes with placental functions residing on proximal chromosomes 2, 7 and 11 and distal chromosome 7 (Cattanach & Kirk 1985, Searle & Beechey 1990, Cattanach et al 1996, McLaughlin et al 1996, 1997. Embryonic growth defects associated with UPD of proximal chromosomes 6 and 18 and distal chromosome 12, in addition to the embryonic lethality associated with UPD of proximal chromosome 17 (Johnson 1974, Winking & Silver 1984, Oakey et al 1995, Beechey 2000, Georgiades et al 2000, Tevendale et al 2006, may also suggest placental defects.…”
Section: Upd and Identification Of Imprinted Regionsmentioning
confidence: 99%
“…The imprinting of these genes plays an important role in prenatal development of multiple tissues, including muscle, bone and brain, and controls postnatal neurological and metabolic functions (Charalambous et al, 2007;Wilkinson et al, 2007). Duplication of maternal distal chromosome 12 along with a deficiency of the corresponding paternal distal portion of the chromosome, MatDp(dist12), causes prenatal growth retardation, hypotrophic immature skeletal muscle and perinatal death (Tevendale et al, 2006); whereas duplication of paternal distal chromosome 12 with deletion of the corresponding maternal region, PatDp(dist12), causes a much more severe phenotype, i.e. death before 16.5 days of gestation (Tevendale et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Duplication of maternal distal chromosome 12 along with a deficiency of the corresponding paternal distal portion of the chromosome, MatDp(dist12), causes prenatal growth retardation, hypotrophic immature skeletal muscle and perinatal death (Tevendale et al, 2006); whereas duplication of paternal distal chromosome 12 with deletion of the corresponding maternal region, PatDp(dist12), causes a much more severe phenotype, i.e. death before 16.5 days of gestation (Tevendale et al, 2006). In humans, uniparental disomy of maternal chromosome 14 (mUPD14) or paternal chromosome 14 (pUPD14) is compatible with life.…”
Section: Introductionmentioning
confidence: 99%